Modernity without a Project - Johnson, C.B (punctum books, 2015)
Entering the 21st century, the postmodern succession has given way to a doom-laden, apolitical orthodoxy. This book offers suggestive readings of "the contemporary" in light of high modernity, postwar modernity, and postmodernity, as framed by the influential institutions of modern art and the spectacles of millennial architecture. Modernity without a Project critiques and connects historical avant-garde currents as they are institutionally expressed or captured, and scrutinizes the remake of New York's Museum of Modern Art, Minoru Yamasaki's vanished Utopias, the "anarchitecture" of Lebbeus Woods, recent work of Rem Koolhaas, delirious developments in Dubai, and the unexpected contribution to architectural debate by the late Hugo Chavez